2007
DOI: 10.1186/1746-4269-3-31
|View full text |Cite
|
Sign up to set email alerts
|

Best practices in intercultural health: five case studies in Latin America

Abstract: The practice of integrating western and traditional indigenous medicine is fast becoming an accepted and more widely used approach in health care systems throughout the world. However, debates about intercultural health approaches have raised significant concerns. This paper reports findings of five case studies on intercultural health in Chile, Colombia, Ecuador, Guatemala, and Suriname. It presents summary information on each case study, comparatively analyzes the initiatives following four main analytical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 8 publications
0
37
0
9
Order By: Relevance
“…Para lograrlo se hace necesario atender las condiciones de exclusión social de la que son objeto, con perspectivas multiculturales y modelos de atención en salud diferenciados, según la etnia y la región, sobre los cuales existen experiencias en Colombia y en América Latina 22,41,60 , que permita superar las barreras existentes para la atención de la salud reproductiva de las mujeres del país, como un deber ético y de justicia social del Estado. Colaboradores C. Noreña-Herrera participó en la concepción del estudio y en todas las etapas de la producción de este artícu-lo y fue el responsable de elaborar la versión de este artículo para ser sometida a publicación.…”
Section: Conclusiónunclassified
“…Para lograrlo se hace necesario atender las condiciones de exclusión social de la que son objeto, con perspectivas multiculturales y modelos de atención en salud diferenciados, según la etnia y la región, sobre los cuales existen experiencias en Colombia y en América Latina 22,41,60 , que permita superar las barreras existentes para la atención de la salud reproductiva de las mujeres del país, como un deber ético y de justicia social del Estado. Colaboradores C. Noreña-Herrera participó en la concepción del estudio y en todas las etapas de la producción de este artícu-lo y fue el responsable de elaborar la versión de este artículo para ser sometida a publicación.…”
Section: Conclusiónunclassified
“…High value of F IC indicates the agreement of selection of taxa between informants, whereas a low value indicates disagreement (Heinrich 2000;Ragupathy et al 2008;Heinrich et al 2009). F IC is used to test the homogeneity among informants knowledge, to test falsifiable hypothesis concerning informant's selection and use of a plant taxa, as a decision-making factor, and to test reliability of traditional knowledge (Heinrich et al 1998;Heinrich 2000;Gazzaneo et al 2005;Njoroge and Bussmann 2006;Almeida et al 2006;Mignone et al 2007;Ragupathy et al 2008;Upadhyay et al 2010). Canales et al (2005) have shown experimentally that the plant species having high F IC value possesses higher antibacterial activity in comparison to species having low F IC value.…”
mentioning
confidence: 99%
“…As the benefits of intercultural initiatives have been demonstrated in other cultural contexts [42], the development of cultural competence in Eeyou Istchee with a focus on providers' communication skills and opportunities to exchange knowledge bilaterally could improve the autonomy of patients and health professionals. Valuing Indigenous knowledge and local implicit protocols of communication may lead to an increase in trust and efficiency.…”
Section: Discussionmentioning
confidence: 99%